Description of a new species of Aclastus Förster (Hymenoptera: Ichneumonidae: Cryptinae) from the Peruvian Andes, with dimorphic females - Bordera, Santiago; Mazon, Marina (Zootaxa, 2015)
The aim of this paper is to describe and illustrate a new species of Aclastus with dimorphic females and to provide the diagnostic characters to distinguish it from Holarctic species of the genus. In addition, we provide data on the habitat and phenology of the species.